Postpartum Fallow Up on the Postpartum Depression after Normal Vaginal Delivery - Soraya Soheili; Razieh Peyghambardoost (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk)
Introduction: The postpartum period is a dangerous potential time for postpartum depression. Postpartum depression is the reducer instrument for postpartum support. The purpose of the current study is to determine the effectiveness of postpartum supports on the postnatal women depression after childbirth. Methods: This study a semi experimental study was conducted in Marand hospital. Two hundred sixty mothers agreed to take part and were randomly allocated to an intervention group (n = 130) or control group (n = 130). The intervention group received telephone counseling for 20- minute at the first week twice, second week till 6th weeks once at week plus routine care. The control group received only the routine care. Also for evaluation of the unanticipated mother’s needs, 24-hour telephone access to researcher was provided. The main outcome measure was recording demographics data sheet, postpartum problem’s checklist and the Edinburgh Postnatal Depression Scale (EPDS) administered by presence interview questionnaire at six weeks after delivery. Control group received general postpartum education. The data were analyzed by χ², Fisher test and T test. Results: At 6 week postpartum, mean of depression was obtained in the intervention group (15/80 ± 5/12) and in the control group (18/43 ± 5/90). On the EPDS scale, in the intervention group was significantly decrease to control group (P < 0.0001). Conclusions: The result of this research showed that Postpartum Fallow Up by midwife could effective to decrease women’s postpartum depression in the pureperium.